ANTISIPASI HUKUM TATA NEGARA DALAM UPAYA MEMPERTAHANKAN INTEGRASI BANGSA INDONESIA - Arinanto, Satya (Jurnal Bestari, 2001)
For a torn country successfully to redefine its civilizational indentity, at least three requirements must be met. First , the political and economic elite of the country has to be generally sypportive of and enthusiastic about the move second, the public has to be at least willing to acquiesce in the redefinition of identity. Third, the dominant elements in the host civilization,in most cases the West, have to be willing to embrace the convert. The process of identity redefinition will be prolonged, interrupted, and painfull, politically, socially, institutionally, and culturally. It also to date has failed.